2019
DOI: 10.20944/preprints201901.0060.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Need for Physical Rehabilitation: Systematic Analysis from the Global Burden of Disease Study 2017

Abstract: Background: To inform global health policies and resources planning, this paper analyzes evolving trends in physical rehabilitation needs, using data on Years Lived with Disability (YLDs) from the Global Burden of Disease Study (GBD) 2017. Methods: Secondary analysis of how YLDs from conditions amenable to physical rehabilitation have evolved from 1990 to 2017, for the world and across countries of varying income levels. Linear regression analyses were used. Results: A 66.2% growth was found in estimated YLD C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
(84 reference statements)
1
21
0
Order By: Relevance
“…It has been reported that the proportion of beneficiaries who experienced a stroke accounted for 25.8% of the total number of beneficiaries [ 38 ]. In addition, neurological diseases, such as stroke and Parkinson’s disease, require continuing physical rehabilitation [ 42 ]. Therefore, educational programs should be developed and implemented with a focus on disease management—the area identified for which HVNs have the greatest educational need, at present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the proportion of beneficiaries who experienced a stroke accounted for 25.8% of the total number of beneficiaries [ 38 ]. In addition, neurological diseases, such as stroke and Parkinson’s disease, require continuing physical rehabilitation [ 42 ]. Therefore, educational programs should be developed and implemented with a focus on disease management—the area identified for which HVNs have the greatest educational need, at present.…”
Section: Discussionmentioning
confidence: 99%
“…There is presently no pharmaceutical treatment for sarcopenia, making physical therapy a key component of the management of this condition. Given that access to physiotherapy may be limited in LMICs [49], general practitioners and other health professionals should promote an increase in levels of physical activity (resistance and strength exercises) in patients diagnosed with or at risk for sarcopenia. As increasing physical activity in older adults may also directly reduce the risk of dementia [50], promotion of physical activity may have a dual positive effect of addressing or preventing both sarcopenia and dementia in LMICs.…”
Section: Clinical Implications and Directions For Future Researchmentioning
confidence: 99%
“…Rehabilitation is unique in its contribution to this public health agenda because of its focuses on optimizing function. In fact, Jesus et al [4] reported that the need for physical medicine and rehabilitation services has been increasing significantly in per capita terms as is the percentage of total years lived with disability globally and across countries of varying income levels. These authors also highlighted that this growth was greater in lower-income countries where rehabilitation is underresourced, emphasizing the pressing needs in these countries.…”
Section: In Order To Encourage Its Wide Dissemination This Article Ismentioning
confidence: 99%